PENGARUH MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION (ATI) DAN POSISI TEMPAT DUDUK SISWA TERHADAP HASIL BELAJAR MATEMATIKA KELAS X SMA NEGERI 1 KUTA - Edy Hermawan; IB. Pt. Esa Wiadnyana (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
This study aimed to determine the effect of learning model Aptitude Treatment Interaction and the seating position to the result learning math class X SMA Negeri 1 Kuta, Which learning model will give different results better learning.This type of research study quasy Experiment (quasi-experimental) design Treatment By Subject where the study population is all students of class X SMA Negeri 1 Kuta which consists of 7 classes. The samples in this study conducted by random sampling technique. From the seventh grade class earned the samples were taken four classes X4, X5, X6, X7 subsequently taken two classes as the experimental group obtained grade X4 and X6 class and second class as the control group gained grade class X5 and X7. Instrument in this study using a test in narrative form while the data analysis used ANOVA F-test two paths. Based on the analysis of data obtained: 1) There perbedeaan atara Math results of students who take the learning model Aptitude Treatment Interaction with students who take the conventional learning models. 2) There perbedeaan results atara Math students in a sitting position with a U-shape with the students sitting position parallel or regular. 3) There is no effect of interaction between the learning model that is applied to the seating position of learners in their influence on mathematics result learning that were not followed by the Tukey test.